Prevalence of Malaria among Infants and Children with febrile illness: A Hospital Based Study - Shakil Ahmad; Farhat Banu; Kamal Raj Sharma; Pooja Thapaliya; Prativa Subedi (Journal of Karnali Academy of Health Sciences, 2021)
Background: About half of the world’s population is at risk of malaria and the burden is particularly high in low-income countries like Nepal. Infants and children are more vulnerable to malaria. Acute febrile illness is the commonest presentation of malaria. Since it is one of the major causes of persistent febrile illnesses in Nepal, empirical antimalarial therapy is usually practiced, especially the endemic areas. A better understanding of the prevalence and clinical profile of malaria helps to tailor the treatment accordingly in cases of undifferentiated febrile illnesses and make the sue of antimalarials more rational.